Anti-quorum sensing activities of selected soil bacteria and chinese herbs and efficiency of electrotransformation by cosmid PLAFR1 vector - Loke, Wai Keong (2020)
Chromobacterium violaceum is a pathogenic bacterium to human and distinctly characterized by the production of a purple pigment called violacein. They are commonly found in soil and water in tropical and subtropical areas. From this study, C. violaceum was found in 0-5 cm depth from the soil surface in Universiti Putra Malaysia golf course and football field with higher density after rainy day. Chromobacterium violaceum also show the characteristics of oligophile, resistant to chlorinated water and antimicrobial activity which allow growing in wider soil and water areas. In both methods (Interaction and Noninteraction), C. violaceum reached quorum level produced antibiotics and inhibited all the selected plant growth-promoting rhizobacteria (PGPR) which were (Azospirillum brasilense Sp7, Rhizobium UPMR1102 and Bacillus sphaericus UPMB10) but did not inhibit the selected PGPR in concentration below their quorum level. These incidences indicate the ubiquitous presence of C. violaceum in Malaysia soils. It would contaminate in the daily use of soil and has potential threats to agriculture sector. One of the bacteria (Bacillus subtilis) randomly isolated from soil was screened based on selective media HiCrome Bacillus Agar. Bacillus subtilis showed the capability of resistancy and antiquorum sensing activity to C. violaceum wild type and mutant type CV026 by inhibiting the production of violacein and resistant to antibiotics produced by C. violaceum. However, screening the genes of interest by pCC1FOS fosmid vector found that none of the clones contained the characteristics desired from the B. subtilis and there were many factors causing the failure of screening in this research. Gene expression from heterologous in new host was facing many limitations and challenges in recent years. Traditional chinese herbs were proven of their anti-quorum sensing activities. Six selected traditional chinese herbs were screened for anti-quorum sensing activity by using C. violaceum as biomonitor. Two out of these herbs were found to exhibit antiquorum sensing properties: Lycium barbarum and Zingiber officinale. Extracts from L. barbarum has stronger anti-quorum sensing activity than Z. officinale. Colonies of C. violaceum treated with L. barbarum almost fully loss its purple pigment. The loss and lack of purple colour from the colonies of C. violaceum indicated that quorum sensing activity was inhibited by the herbal extraction. It was believed that these herbs contained a rich source of compounds to fight or control pathogenic bacteria and potentially a new therapeutic way to reduce the development of antibiotic resistance. In electrotransformation, a large size of cosmid vector was successfully transferred into the selected PGPR and C. violaceum by using electroporation. These methods were found to be more efficient by using lower field strength with longer pulse length. The cosmid vector from donor E. coli K12 MM294 was also a success by direct transferred to the recipients A. brasilense Sp7 and C. violaceum by electroduction.